WRITTEN CORRECTIVE FEEDBACK PRACTICES IN SENIOR HIGH SCHOOLS IN GHANA - Mensah, Dorah; Owu-Ewie, Charles; Abunya, Levina Nyameye; Abban, Albert (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This paper examines the practice of written error correction from different perspectives in real classroom contexts. Although a plethora of research has been done in different contexts, the subject is least exploited in Ghana, especially in senior High school contexts. This paper reports on a qualitative study of written corrective feedback practices in three Senior High schools in Ghana. Drawing on Schmidt’s noticing hypothesis and Swain’s comprehensive output hypothesis models, the study aims to determine whether teachers’ written error corrections effectively direct students towards ‘noticing’ the gaps in their written ‘output’, thereby resulting in higher degrees of learnability. A sample size of 824 students was selected from five common course areas using a systematic random sampling strategy, while a purposive sampling strategy was used to select nine English language teachers who had at least three years of continuous experience from the three schools. The findings of the study indicate that teachers have positive beliefs about the potency of written error corrections in the development of language. However, variances in the choice of strategies, practices of teachers, and preferences of students result in the provision of non-targeted feedback which affects revision and learnability. This study recommends that teachers should collaborate with learners to provide more targeted corrections which would result in enhanced ‘noticing’ and improved learnability of the English language among Ghanaian students.